Depiction of a Ganesha icon - Temples of India Project Team (Jio Institute, 2024)
Seen here is another face of the sarvatobhadra (open from all sides), which features a depiction of a Ganesha icon. The four-handed image is depicted in a sitting posture, although the specific attributes of the icon are difficult to identify. The niche containing the Ganesha icon is topped by a pyramidal shikhara (superstructure). The Ganesha icon is characterized by long elongated ears, and the trunk curls up to rest on a bijapuraka (citron fruit).